Knowledge Transfer Through Inheritance: Spin-Out Generation, Development, and Survival - Agarwal, Rajshree; Echambadi, Raj; Franco, April; Sarkar, MB (Academy of Management Journal, 2004)
We investigated how the knowledge capabilities of industry incumbents affected the generation, development, and performance of ?spin-outs? (entrepreneurial ventures of ex-employees). Analyses of 1977?97 data from the disk drive industry supported our hypothesis that incumbents with both strong technological and market pioneering know-how generate fewer spin-outs than firms with strength in only one of these areas. Also, an incumbent?s capabilities at the time of a spin-out?s founding positively affect the spin-out?s knowledge capabilities and its probability of survival.